Characterization of ASKP1240, a Fully Human Antibody Targeting Human CD40 With Potent Immunosuppressive Effects. Issue 6 (14th April 2014) - Okimura, K.; Maeta, K.; Kobayashi, N.; Goto, M.; Kano, N.; Ishihara, T.; Ishikawa, T.; Tsumura, H.; Ueno, A.; Miyao, Y.; Sakuma, S.; Kinugasa, F.; et al.
<x xml:space="preserve">Abstract</x> Blocking the CD40–CD154 interaction is reported to be effective for transplantation management and autoimmune disease models in rodents and nonhuman primates. However, clinical trials with anti‐CD154 mAbs were halted because of high incidence of thromboembolic complications. Thus, we generated and characterized a fully human anti‐CD40 mAb ASKP1240, as an alternative to anti‐CD154 mAb. In vitro ASKP1240 concentration‐dependently inhibited human peripheral blood mononuclear cell proliferation induced by soluble CD154. In addition, ASKP1240 did not destabilize platelet thrombi under physiological high shear conditions while mouse anti‐human CD154 mAb (mu5C8) did. And ASKP1240 itself did not activate platelet and endothelial cells. In vivo administration of ASKP1240 (1 or 10 mg/kg, intravenously) to cynomolgus monkeys, weekly for 3 weeks, significantly attenuated both delayed‐type hypersensitivity and specific antibody formation evoked by tetanus toxoid. The immunosuppressive effect was well correlated with the CD40 receptor saturation. Thus, these results suggest that ASKP1240 is immunosuppressive but not prothromboembolic, and as such appears to be a promising therapeutic candidate for the management of solid organ transplant rejection and autoimmune diseases therapy.